Strategi Pengembangan Desain dalam Pembelajaran Daring di Era Budaya Digital - Magdalena, Ina; Hadi, Awal Septian; Luthfia, Luthfia (Lembaga Yasin AlSys, 2023)
Technological developments are increasingly advanced and growing rapidly. Likewise with virtual online learning applications, software and hardware technology and supporting infrastructure. The strategy for developing online learning in the era of digital culture is measured based on three strategies, including focusing on technology, being involved in the social environment (social context), and utilizing the web. What is prepared for learning media is an online platform, including video conferencing media via zoom, Google meet or other means of discussion, internet connection, and others. Not only teacher students must also undergo training in technology so they can master the online platform. E-learning is one of the selected media because with e-learning students get new knowledge that they can, and students can share information with each other and can access learning materials at any time and repeatedly. students can further strengthen their mastery of learning material.